Physiotherapists' perceptions of how patient adherence and non-adherence to recommended exercise for musculoskeletal conditions affects their practice: a qualitative study. (December 2021) - Room, Jonathan; Boulton, Mary; Dawes, Helen; Archer, Kirsty; Barker, Karen
Abstract: Objectives: The aim of this study was to explore physiotherapists' perceptions of how patients' adherence and non-adherence to recommended exercise affects their practice. Design: A qualitative study with a focus group and semi-structured interviews. The focus group and interviews were audio recorded and transcribed verbatim. Transcripts were analysed using thematic analysis. Setting: MSK physiotherapy services in the United Kingdom. Participants: Focus group: 8 UK registered physiotherapists (age range = 24–48; seven female, one male). Semi-structured interviews: 10 UK registered physiotherapists (age range = 28–52; eight female, two male). Results: Participants described how exercise adherence could be a challenging aspect of clinical practice and how they tried to improve it. Four main themes were identified: 1) A challenge but worth it; 2) It's frustrating but you can't win them all; 3) Striving to see the individual; and 4) Striving to help the patient. The importance of establishing a good working relationship with patients was emphasised. This included working collaboratively with the patient, avoiding blaming them for non-adherence and thinking about the language they used in discussing exercises. Conclusion: Patient non-adherence to recommended exercise is a challenging aspect of clinical practice. Physiotherapists can acknowledge this difficulty, and the frustrations it may potentially bring, yet remain resilient in the face of it. Clinicians should consider potential approaches and strategies to optimise the potential for behaviour change, and to improve exercise adherence. Robust interventions to help clinicians facilitate better exercise adherence are also needed.